2001
DOI: 10.1046/j.1365-2249.2001.01512.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-galectin-1 autoantibodies in humanTrypanosoma cruziinfection: differential expression of thisβ-galactoside-binding protein in cardiac Chagas' disease

Abstract: SUMMARYThe pathogenesis of Chagas' disease has been subject of active research and still remains to be ascertained. Galectin-1 (Gal-1), a member of a conserved family of animal b-galactoside-binding proteins, localized in human heart tissue, has been suggested to play key roles in immunological and inflammatory processes. In the present study we demonstrated the occurrence of anti-Gal-1 autoAb in sera from patients in the acute and chronic stages of Chagas' disease (ACD and CCD) by means of ELISA and Western b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 45 publications
3
37
0
4
Order By: Relevance
“…Previous studies demonstrated the expression of Gal-1 in T. cruzi-infected immune cells (35,36). Moreover, in human settings, this lectin has been shown to be prominently expressed in cardiac tissue from patients with severe chronic Chagas' disease (50). In this study, we demonstrate a tolerogenic role for Gal-1 during acute T. cruzi infection.…”
Section: Discussionsupporting
confidence: 55%
“…Previous studies demonstrated the expression of Gal-1 in T. cruzi-infected immune cells (35,36). Moreover, in human settings, this lectin has been shown to be prominently expressed in cardiac tissue from patients with severe chronic Chagas' disease (50). In this study, we demonstrate a tolerogenic role for Gal-1 during acute T. cruzi infection.…”
Section: Discussionsupporting
confidence: 55%
“…We have previously shown that anti-Gal-8 autoantibodies produced by SLE patients block the interaction of Gal-8 with β1 integrins involved in its apoptotic action upon activated T cells (Norambuena et al, 2009). Autoantibodies against diff erent members of the galectin family such as Gal-1, -2, -3, and -4 been detected in patients with diff erent types of autoimmune diseases and in cancer (Lutomski et al, 1997;Giordanengo et al, 2001;Jensen-Jarolim et al, 2001;Lim et al, 2002;Romero et al, 2006;Montiel et al, 2010). However, whether autoantibodies against galectins interfere with galectin function in the immune system and whether they play pathogenic roles are poorly studied.…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous galectin-1 expression is up-regulated in vitro and in vivo by T. cruzi, and the expression of galectin-1 is up-regulated in cardiac tissue from patients with chronic Chagas disease (31). Because the adhesion of T. cruzi to heart muscle cells is mediated by protein-carbohydrate interactions, an overexpression of galectin-1 on heart tissue could facilitate parasite invasion toward this vulnerable infection site (32).…”
Section: Discussionmentioning
confidence: 99%